2015
DOI: 10.3390/ijms161024139
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chemotherapeutic Activity by Morus alba Fruits through Immune Response of Toll-Like Receptor 4

Abstract: Morus alba L. fruits have long been used in traditional medicine by many cultures. Their medicinal attributes include cardiovascular, hepatoprotective, neuroprotective and immunomodulatory actions. However, their mechanism of macrophage activation and anti-cancer effects remain unclear. The present study investigated the molecular mechanisms of immune stimulation and improved chemotherapeutic effect of M. alba L. fruit extract (MFE). MFE stimulated the production of cytokines, nitric oxide (NO) and tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…The binding of polysaccharides to TLR4 is a critical event in immune activation (Tewari et al, 2017). iNOS and TNF-α signalling pathway is activated by TLR4 and transduced via mitogen-activated protein kinases MAPKs (ERK, p38 and JNK), NFκB as well as a Janus tyrosine kinase (JAK) and signal transducers and activators of transcription (STATs) (Chang, Kim, Lee, Park, & Kim, 2015;Zhou et al, 2015). PPGT was found to increase the phosphorylation of ERK, JNK, p38, IKK, and STAT-1 in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of polysaccharides to TLR4 is a critical event in immune activation (Tewari et al, 2017). iNOS and TNF-α signalling pathway is activated by TLR4 and transduced via mitogen-activated protein kinases MAPKs (ERK, p38 and JNK), NFκB as well as a Janus tyrosine kinase (JAK) and signal transducers and activators of transcription (STATs) (Chang, Kim, Lee, Park, & Kim, 2015;Zhou et al, 2015). PPGT was found to increase the phosphorylation of ERK, JNK, p38, IKK, and STAT-1 in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 (1 × 10 5 cells/well) were incubated in a 96-well plate with 10, 30, or 100 μg/mL PPGT for 24 h. NO was measured by determining the concentration of nitrite, its stable oxidative metabolite, using a microplate assay according to a previously described method (Chang et al, 2015).…”
Section: No Assaymentioning
confidence: 99%
“…Moreover, NF‐κb up‐regulation enhances T‐cell immunity . MFE can increase NK cell and cytotoxic T‐lymphocyte activity by activating NF‐κb to generate IFN‐γ . Medicines can also suppress NF‐κb to inhibit the immune response, which leads to carcinoma cell escape .…”
Section: Discussionmentioning
confidence: 99%
“…43 MFE can increase NK cell and cytotoxic T-lymphocyte activity by activating NF-κb to generate IFN-γ. 44 Medicines can also suppress NF-κb to inhibit the immune response, which leads to carcinoma cell escape. 45 Our results indicated that the addition of FSTL1 downregulated JNK expression, thereby enhancing immune activity ( Figures 4C and 4E).…”
Section: Discussionmentioning
confidence: 99%
“…Morus alba L. (white mulberry), found in Asia, has been traditionally used in Korea [55]. When orally given to BALB/c mice bearing CT26 colon tumors for 3 weeks, M. alba L. fruit extract (MFE) at a dose of 300 mg/kg of body weight, which was equivalent to 24.3 mg/kg human body weight, has been shown to significantly enhance the anti-tumor activity when in combination with 5-fluorouracil, and strongly promote NK cell activity, cytotoxic T lymphocyte activity, and IFN-γ production in spleen [55].…”
Section: Studies Of Tumor-bearing Animal Modelsmentioning
confidence: 99%